Code unknown : an incomplete account of various journeys [videorecording (DVD)] - Haneke, Michael, 1942-; Binoche, Juliette, 1964-; Neuvic, Thierry; Bierbichler, Josef (Criterion collection, 2015)
Composed almost entirely of brilliantly shot, single-take vignettes focusing on characters connected to one seemingly minor incident on a Paris street, Haneke's film, with an outstanding international cast is a revelatory take on racial inequality and the failure of communication in today's increasingly diverse European landscape.